Design of near optimal user interface with minimal UI elements using evidence based recommendations and multi criteria decision making: TOPSIS method. (2018) - Vairamuthu, Subbiah; Anouncia, S. Margret
One among the research challenges in human computer interaction (HCI) is to build user interfaces in the way that make users satisfy. This would improve the usability of an information system. In general, usability is one of the non-functional requirements which decides the acceptability. Usability factors when not considered properly during interaction design will lead spending more cost and time for any organisation. Simple interaction styles with guiding user interface components for navigations will improve the users' interaction. The improved interaction thus would facilitate in improving the users satisfaction towards using any information system. In this work, it has been attempted to recommend designers to build user interface with minimal components without compensating the effectiveness. For this process, the multi criteria decision making (MCDM) approach technique for order preference by similarity to ideal solution (TOPSIS) was employed in this work.